Scope of Evidence Based and Cognitive Based Medicine in Homoeopathy (Advancements in Homeopathic Research, 2022)
Homoeopathy is one of the most popular alternative medical modality sought for in the world. India has the highest number of qualified homoeopathic doctors highest effectiveness both in the private and public sector.While the Government Health Sectors are making major forays into research especially by the Central Council for Research in Homoeopathy [CCRH], private research is lagging behind inspite of a large pool from amongst the private and independent sectors, the clinicians, practitioners and small scale independent organisations. This pool is truly a sector from where the “Big Data” has to be harnessed into a format that will help the scientific forums to comprehend and analyse.Two of the current and most widely accepted scientific study protocols that will help achieve the professionalism that Homoeopathy deserves are the Evidence Based Medicine [EBM] and Cognition Based Medicine [CBM].While EBM is the “conscientious, explicit, and judicious use of current best evidence in making decisions aboutthe care of individual patients.”, the primary element of CBM is the criteria-based assessment of therapeutic causality at the level of the individual patient. This method offers an exceptional opportunity for Homoeopathy, even for the independent Clinicians to hone their research writing skills and to find a rational process to capture the relationship of the ‘gestalt’ in the causality and effect which has always been a grey area in Homoeopathy.
Keywords: Homoeopathy in India-large pool of Clinicians-Big Data-EBM; CBM- Ideal opportunity for Research in Homoeopathy